Explaining the Biasing Effects of Performance Cues in Terms of Cognitive Categorization - Binning, John F.; Zaba, Andrea J.; Whattam, John C. (Academy of Management Journal, 1986)
Previous research has consistently demonstrated that observers' ratings of various phenomena related to group processes are significantly biased when raters get bogus feedback about a group's performance before the rating task. This study strengthens Phillips and Lord's (1982) explanation of this bias and tests McElroy and Downey's (1982) alternative explanation. Results indicate that ratings of both specific observable behaviors and global evaluations are biased in the direction of performance cues. A rated behavior's relation to observers' conceptions of good and poor leadership explains such bias better than observability.